Flexible and Ultrasoft Inorganic 1D Semiconductor and Heterostructure Systems Based on SnIP. (13th March 2019) - Ott, Claudia; Reiter, Felix; Baumgartner, Maximilian; Pielmeier, Markus; Vogel, Anna; Walke, Patrick; Burger, Stefan; Ehrenreich, Michael; Kieslich, Gregor; Daisenberger, Dominik; Armstrong, Jeff; Thakur, Ujwal Kumar; et al.
Abstract: Low dimensionality and high flexibility are key demands for flexible electronic semiconductor devices. SnIP, the first atomic‐scale double helical semiconductor combines structural anisotropy and robustness with exceptional electronic properties. The benefit of the double helix, combined with a diverse structure on the nanoscale, ranging from strong covalent bonding to weak van der Waals interactions, and the large structure and property anisotropy offer substantial potential for applications in energy conversion and water splitting. It represents the next logical step in downscaling the inorganic semiconductors from classical 3D systems, via 2D semiconductors like MXenes or transition metal dichalcogenides, to the first downsizeable, polymer‐like atomic‐scale 1D semiconductor SnIP. SnIP shows intriguing mechanical properties featuring a bulk modulus three times lower than any IV, III‐V, or II‐VI semiconductor. In situ bending tests substantiate that pure SnIP fibers can be bent without an effect on their bonding properties. Organic and inorganic hybrids are prepared illustrating that SnIP is a candidate to fabricate flexible 1D composites for energy conversion and water splitting applications. SnIP@C3 N4 hybrid forms an unusual soft material core–shell topology with graphenic carbon nitride wrapping around SnIP. A 1D van der Waals heterostructure is formed capable of performing effective water splitting. Abstract : SnIP, an atomic‐scale double helix semiconductor, shows a Young's modulus like steel upon bending perpendicular to the double helix axis and a bulk modulus three times lower than any inorganic IV, III‐V, or II‐VI semiconductor. Such flexibility qualifies SnIP for flexible semiconductor devices. Self‐assembled SnIP@C3 N4 hybrids create effective heterojunctions for water splitting.